Interactions of an Essential Bacillus subtilis GTPase, YsxC, with Ribosomes - Wicker-Planquart, Catherine (American Society for Microbiology (ASM), 2008)
YsxC is a small GTPase of Bacillus subtilis with essential but still unknown function, although recent works have suggested that it might be involved in ribosome biogenesis. Here, purified YsxC overexpressed in Escherichia coli was found to be partly associated with high-molecular-weight material, most likely rRNA, and thus eluted from gel filtration as a large complex. In addition, purification of ribosomes from an E. coli strain overexpressing YsxC allowed the copurification of the YsxC protein. Purified YsxC was shown to bind preferentially to the 50S subunit of B. subtilis ribosomes; this interaction was modulated by nucleotides and was stronger in the presence of a nonhydrolyzable GTP analogue than with GTP. Far-Western blotting analysis performed with His(6)-YsxC and ribosomal proteins separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed that YsxC interacted with at least four ribosomal proteins from the 50S subunit. Two of these putative protein partners were identified by mass spectrometry as L1 and L3, while the third reactive band in the one-dimensional gel contained L6 and L10. The fourth band that reacted with YsxC contained a mixture of three proteins, L7/L12, L23, and L27, suggesting that at least one of them binds to YsxC. Coimmobilization assays confirmed that L1, L6, and L7/L12 interact with YsxC. Together, these results suggest that YsxC plays a role in ribosome assembly.